2020
DOI: 10.1002/jmv.26652
|View full text |Cite
|
Sign up to set email alerts
|

Short‐duration treatment with the novel non‐nucleoside inhibitor CDI‐31244 plus sofosbuvir/velpatasvir for chronic hepatitis C: An open‐label study

Abstract: Combination regimens of direct‐acting antiviral agents (DAAs) for chronic genotype 1 hepatitis C virus (HCV) infection given for 8 or 12 weeks have high cure rates. Shortened treatment durations that maintain high cure rates may lessen treatment barriers related to affordability and drug adherence. We enrolled 12 treatment‐naïve adults with chronic genotype 1 HCV infection without cirrhosis in a single‐center, open‐label trial to receive 2 weeks of the highly potent and selective non‐nucleoside inhibitor (NNI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to Chua et al [19], a combination regimens of DAAs for chronic HCV infection given for 8 or 12 weeks, have high cure rates. Treatment durations that are reduced while maintaining high cure rates may reduce treatment barriers related to affordability and drug adherence.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chua et al [19], a combination regimens of DAAs for chronic HCV infection given for 8 or 12 weeks, have high cure rates. Treatment durations that are reduced while maintaining high cure rates may reduce treatment barriers related to affordability and drug adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In a small clinical trial, a novel non-nucleoside reverse transcriptase inhibitor was combined with sofosbuvir/velpatasvir to treat treatment-naïve genome in one patient infected with HCV, using a shortened trial of only six weeks. The trial reported an SVR of 75% amongst the trial participants, thus marking it as a positive step in the researchers' efforts to ameliorate HCV treatment while reducing costs [ 40 ]. Refer to Table 1 for the evolution of drugs for treating HCV.…”
Section: Reviewmentioning
confidence: 99%